Herpesviruses associated with mortalities among Pacific oyster, Crassostrea gigas, in France-Comparative study - Renault, Tristan; Le Deuff, Rose-marie; Cochennec, Nathalie; Maffart, P (Ecole National Vet Toulouse, 1994)
Sporadic mortalities were reported in june and july of 1992 and 1993 among batches of hatchery-reared larval Pacifie oyster, Crassastrea gigas, and at the beginning of July and in August of 1993 among five batches of 3-7 month old young spats, C. gigas. Observations with transmission electron microscope showed the presence of herpes-like virus particles in infected larvae and young spats. The viruses observed in diseased larvae and affected young spat oysters were very similar. Elevated temperature and crowding may increase susceptibility of oysters to these herpes-like virus infections. Des mortalités épisodiques ont été observées au cours des étés 1992 et 1993, parmi des lots de larves d'huître creuse, Crassastrea gigas, élevées en écloserie. Par ailleurs, au début du mois de juillet et au mois d'août 1993, des mortalités sporadiques ont également été enregistrées parmi cinq lots de juvéniles d'huître creuse, C. gigas, âgés de 3 à 7 mois. Des observations en microscopie électronique à transmission ont permis de révéler la présence de particules virales apparentées aux herpesvirus, chez les larves et les juvéniles moribonds. Les virus observés chez les larves et sur le naissain semblent très proches. Les températures élevées et les conditions d'élevage intensif pourraient augmenter la sensibilité des huîtres à ces infections virales.